Phenanthrene Antibiotic Targets Bacterial Membranes and Kills Staphylococcus aureus With a Low Propensity for Resistance Development - Chen, Bo-Chen; Lin, Chang-Xin; Chen, Ni-Pi; Gao, Cheng-Xian; Zhao, Ying-Jie; Qian, Chao-Dong (Frontiers in Microbiology, 2018)
New classes of antibiotics with different mechanisms of action are urgently required for combating antimicrobial resistance. Blestriacin, a dihydro-biphenanthrene with significant antibacterial activity, was recently isolated from the fibrous roots of Bletilla striata. Here, we report the further characterization of the antimicrobial potential and mode of action of blestriacin. The phenanthrene compound inhibited the growth of all tested clinical isolates of Staphylococcus aureus including methicillin-resistant S. aureus (MRSA). The minimum inhibitory concentrations (MICs) of blestriacin against these pathogens ranged from 2 to 8 μg/mL. Minimum bactericidal concentration (MBC) tests were conducted, and the results demonstrated that blestriacin was bactericidal against S. aureus. This effect was confirmed by the time-kill assays. At bactericidal concentrations, blestriacin caused loss of membrane potential in B. subtilis and S. aureus and disrupted the bacterial membrane integrity of the two strains. The spontaneous mutation frequency of S. aureus to blestriacin was determined to be lower than 10-9. The selection and whole genome sequencing of the blestriacin –resistant mutants of S. aureus indicated that the development of blestriacin resistance in S. aureus involves mutations in multi-genes. All these observations can be rationalized by the suggestion that membrane is a biological target of blestriacin.